ANALISIS GETARAN ROTASIONAL TEREDAM SISTEM BATANG DAN PEGAS TORSIONAL UNTUK DIKEMBANGKAN SEBAGAI MODEL FLUKTUASI EKONOMI - Nani Yuningsih; Kunlestiowati Hadiningrum; Sardjito Sardjito (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2017)
The ideal free vibration system is characterized by periodic oscillation motion with fixed amplitude. In fact, towards this kind of vibration system, there is an external force that will dampen the vibration so the amplitude will be decreased continuously. In damped vibrations, in addition to amplitude change, the frequency will also be different from the frequency of free vibration. It has been observed the phenomenon of rotational homogeneous rods attached to torsional spring and occurs damping due to air friction both theoretically and empirically. Basically rotational vibration characteristics are similar to translational vibrations. The observed variables are the deviation angle of the amplitude and the vibration period. Measurements are done by video camera and digital counter. The empirical observations reinforce the solution of the differential equations obtained by theoretical analysis of the damped vibration system. The result of the research on the mechanical rod and spring vibration system was developed to observe the phenomenon of economic fluctuation occurring in Indonesia, using the analogy between physics phenomenon and economic phenomenon (econophysics). Keywords: rotational vibration, torsional spring, econophysics.